Antiretrovirals for low income countries: an analysis of the commercial viability of a highly competitive market - Nakakeeto Olive N; Elliott Brian V (Globalization and Health, 2013)
Abstract Background The price of antiretroviral drugs (ARVs) in low income countries declined steadily in recent years. This raises concerns about the commercial viability of the market of ARVs in low income countries. Methods Using 2 costing scenarios, we modeled the production cost of the most commonly used ARVs in low income countries in 2010 and 2012, and assessed whether, at the median price paid by low income countries, their manufacturers would still make profits. By interviews we consulted 11 generic manufacturers on the current state of the ARV market, and on what would be required to ensure their continued commitment to supply ARVs to low income countries. Results Using the lowest prices for active pharmaceutical ingredients (API) quoted to WHO, and applying published assumptions about the production cost of ARVs, our baseline estimate was that Indian generic manufacturers would have made profits on only 1 out of 13 formulations of ARVs in both 2010 and 2012, and publicly owned manufacturers would have made profits on 5 and 3 out of 13 formulations in 2010 and 2012, respectively. We needed to assume a 20% and a 40% lower API cost for our model to predict that publicly owned and Indian manufacturers, respectively, would make profits on the sale of the majority of their ARVs. Between 2010 and 2012, we estimate that - across the ARV portfolio - the gross profit on sales of ARVs to low income countries decreased with between 6% and 7% of their sales price. Generic manufacturers consider that current prices are unsustainable. They suggested amendments to the tender procedures, simplified regulatory procedures, improved forecasting, and simplification of the ARV guidelines as critical improvements to maintain a viable ARV market. Conclusions While recent price decreases indicate that there is still space for price reduction, our estimate that gross profit margin on sales decreased by 6 to 7% between 2010 and 2012 lends credibility to assertions by generic manufacturers that the ARV market in low income countries is under considerable price pressure. This might create problems for the quality and/or the continued supply of ARVs to low income countries.